Sejmowe komisje Śledcze w systemie politycznym RP. Bilans dotychczasowych doświadczeń - Secler, Bartłomiej (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
The purpose of this paper is to reflect upon the experience related to the appointment and operations of parliamentary commissions of inquiry in Poland. The author ponders whether the commissions appointed so far have contributed to improving the quality of political life and provided reliable explanations of scandals in circles of power, or perhaps they have rather become an instrument of political struggle, allowing political rivals to be easily discredited. The analysis conducted indicates that, on account of the composition of commissions (including politicians), so far their main focus has been political rivalry, instead of the actual investigation of scandals. The author also has reservations about the ineffectiveness of commissions of inquiry, which stems from imperfect legal provisions. The considerations refer to the supervisory function of the Polish parliament.
Parliamentary commissions of inquiry in the political system of contemporary Poland. The experience so far